(untitled) (Indian Journal of Arid Horticulture, 2025)
A study was carried out in a private orchard in Paschim Midnapore district of West Bengal during the period 2006-2008 to find out the best time for propagation of aonla in nursery and field. Another investigation was also made to find out the compatibility of seven cultivars of aonla to wedge grafting in nursery, using rootstock of ’local’ cultivar. Results indicated that wedge grafting to be the best in nursery propagation as it gave higher success (60 to 70 per cent) for a longer period (45th August to 25th September) as compare to budding. The growth of the plant was better when operation was performed in early part of monsoon (i.e., June) in both the cases of budding and grafting. In-situ propagation of aonla considered to be the best way for raising orchard as compare to nursery propagation as it resulted highest success (80%) with better plant growth and suitable time was the last week of June and first week of August. Regarding compatibility of the cultivars to wedge grafting with local cultivar, NA-10 found to show best result by giving 70% success followed by BSR-1, Chakaiya and Neelum (50% success). Growth of the grafted plants was good in most of the cultivars.